The Effect Of Deep Learning Management And Classroom Management Skills On The Mathematics Learning Outcomes Of Junior High School Students In North Langowan District - Mertika Mumu; Jeffry SJ Lengkong; Zoya F. Sumampouw (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Mertika Mumu. 25804030. The Effect of Deep Learning Instructional Management and Classroom Management Skills on the Mathematics Learning Outcomes of Junior High School Students in North Langowan District. Supervised by Prof. Dr. Jeffry SJ Lengkong, M.Pd and Dr. Zoya F. Sumampouw, M.Pd. Master's Program in Educational Management, Graduate School, Manado State University. This study aims to determine and analyze (1) the effect of deep learning instructional management on the mathematics learning outcomes of junior high school students in North Langowan District, (2) the effect of classroom management skills on the mathematics learning outcomes of junior high school students in North Langowan District, and (3) the effect of deep learning instructional management and classroom management skills simultaneously on the mathematics learning outcomes of junior high school students in North Langowan District. The population of this study consisted of all students of SMP Negeri 3 Langowan and SMP Negeri 9 Langowan, totaling 160 students. The sample consisted of 61 students selected using proportionate stratified random sampling technique. The data collection method used in this study was a questionnaire. The data were analyzed using simple regression analysis and multiple regression analysis. The results of the study show that (1) deep learning instructional management has an effect on students' mathematics learning outcomes by 50.22%, (2) classroom management skills have an effect on students' mathematics learning outcomes by 56.44%, and (3) deep learning instructional management and classroom management skills simultaneously have an effect on students' mathematics learning outcomes by 64.2%. Keywords: Deep Learning Instructional Management, Classroom Management Skills, Mathematics Learning Outcomes.